Students' Perception on Online vs. Offline Learning at English Department of UNP - Lestari, Ira; Rani, Yati Aisya (Universitas Negeri Padang, 2024)
This study aimed to determine students' perceptions of the implementation of online and offline learning experiences. This research used a quantitative method. The sample of this study was students of 2021 at English Department of UNP who were selected through a proportional random sample. Questionnaires were used to collect data. Students' perceptions were analyzed from several dimensions namely Course Structure and Organization, Learner Interaction, Instructor Presence, Student Engagement, Student Satisfaction and Perceive Learning. The results of the analysis showed that there was a negative perception of Learner Interaction, while the other aspects of the dimension showed positive results.